Geobiological and diagenetic insights from Malvinokaffric Devonian biota (Chapada group, Paraná Basin, Brazil): Paleobiological and paleoenvironmental implications - Becker-Kerber, Bruno; Ladeiraosés, Gabriel; Curado, Jessica Fleury; De Almeida Rizzutto, Márcia; Rudnitzki, Isaac Daniel; Romero, Guilherme Raffaeli; Onary-Alves, Silvio Yuji; Benini, Victoria Giopato; Galante, Douglas; Rodrigues, Fabio; Buck, Pedro Victor; Rangel, Elidiane Cipriano [UNESP]; et al. (Society for Sedimentary Geology, 2017)
This study tests the presence of differential preservation in the Devonian Malvinokaffric fauna from the Chapada Group (Paraná Basin, Brazil). Results of EDXRF, EDS, Raman Spectroscopy, and petrographic analyses show differential preservation of shells that were originally calcite as hematite and goethite fossils, while organisms with original calcium phosphate shells tend to be preserved inside phosphatic concretions. Both preservation types are commonly associated with pseudoframboids, while calcium sulfate minerals are commonly associated with hematized fossils. From this evidence, a diagenetic model for these fossils is proposed. The model includes an early diagenetic phase (characterized by anaerobic sulfate reduction and precipitation of pyrite and carbonate-fluorapatite) and a second, near-surface chemical weathering phase (characterized by the oxidation of pyrite and precipitation of iron oxyhydroxides and calcium sulfates). Acidic conditions in both phases may account for the dissolution of less stable minerals compared to calcium phosphate. It is considered that this model may assist in understanding other similarly preserved biotas, as well as enhancing understanding of the taphonomic overprint that may occur within this important and endemic Devonian biota.